FORTY YEARS SINCE THE CHORNOBYL NUCLEAR POWER PLANT ACCIDENT THROUGH THE POSTERS OF STUDENT DESIGNERS - Kazimirenko, Olena (Young Scholars Grinchenko – Seton International Journal, 2026)
April 26, 1986, divided the life of the then-Soviet Ukraine into before and after the accident at the Chornobyl Nuclear Power Plant. In 2026, students of the Applied College "Universum" of Borys Grinchenko Kyiv Metropolitan University, majoring in "Design", investigated the public's views on the historical aspects of the events and on modern life in the radiation-contaminated zone. The article presents the students' posters as an illustration of their research.